IMPLEMENTATION OF DEEP LEARNING IN ISLAMIC RELIGIOUS EDUCATION (PAI) LEARNING IN MADRASAH - Khoiri; Abdul Rasyid M. Akib (Indonesian Journal of Islamic Studies (IJIS), 2025)
The development of artificial intelligence (AI) technology, especially deep learning, has made significant contributions in various fields, including the world of education. In the context of Islamic Religious Education (PAI), the biggest challenge today is how to deliver teaching materials effectively, adaptively, and relevant to the development of the times and the characteristics of the digital generation. Deep learning implementations offer a variety of opportunities to support a more personalized, interactive, and efficient learning process. Through an algorithm-based approach, deep learning is able to process student learning data to provide a learning experience tailored to individual learning styles. The application of this technology also allows for automatic assessment of students' understanding through text, voice, and expression analysis, so that teachers can focus more on providing character development and spiritual values. On the other hand, the use of AI-based chatbots and intelligent assistants can facilitate discussions and consultations about Islamic teachings instantly and factually. The methodology used in this study is a descriptive qualitative study with a literature study and case study approach. Data were collected through a review of national and international scientific literature and focused observations on the practice of AI implementation in several madrassas and Islamic schools in Indonesia. The analysis was carried out thematically by identifying patterns, opportunities, and challenges of applying deep learning in PAI learning. The results of this study are expected to make a scientific contribution to the development of technology-based Islamic education in the digital era.